Pregnancy outcomes in association with placental histopathology in pregnancies complicated by macrosomia in diabetic vs. non-diabetic women. (May 2020) - Kleiner, Ilia; Ram, Shai; Kovo, Michal; Schreiber, Letizia; Barber, Elad; Levy, Michal; Fainstein, Nataly; Bar, Jacob; Weiner, Eran
Abstract: Objective: We aimed to compare pregnancy outcomes in association with placental pathology in pregnancies complicated by macrosomia in diabetic vs. non-diabetic women. Study design: Pregnancies complicated by macrosomia (≥4000gr) were included. Pregnancy and delivery characteristics, neonatal outcomes and placental histopathology reports were compared between macrosomia in diabetic [pre-gestational or Gestational Diabetes Mellitus (GDM)] women (diabetic-macrosomia group) vs. non-diabetic women (non-diabetic macrosomia group). Adverse neonatal outcome was defined as ≥1 neonatal complications. Multivariate analysis was used to identify independent associations with adverse neonatal outcome. Results: The diabetic macrosomia group (n = 160) was characterized by higher maternal age (p = 0.002), Body Mass Index (BMI) (p < 0.001), and smoking (p = 0.03), and lower gestational age at delivery (p = 0.001). The diabetic-macrosomia group had higher rates of scheduled Cesarean deliveries (CDs) (58.9 % vs23.7 %, p < 0.001) while the non-diabetic macrosomia group (n = 214) had higher rates of emergent CDs (76.3 % vs.40.7 %, p < 0.001), perineal tears (p = 0.027) and Post Partum Hemorrhage (PPH) (p = 0.006). Placentas from the non-diabetic macrosomia group were characterized by higher rates of maternal and fetal inflammatory response lesions (p < 0.001). Except for higher jaundice rate in the diabetic macrosomia group (p < 0.001), none of the other neonatal outcomes including shoulder dystocia differed between the groups. In multivariate analysis GA < 37 weeks (aOR = 1.4, 95 %, CI-1.2–3.9), and emergent CDs (aOR = 1.7, 95 %, CI-1.4–4.1) but not diabetes (aOR = 1.1, 95 %, CI-0.7–3.9) were associated with adverse neonatal outcome. Conclusions: Despite major differences in maternal demographics, mode of delivery, maternal morbidity, and placental characteristics- adverse neonatal outcome did not differ between macrosomia in diabetic vs. non-diabetic women and was high in both groups. Clinicians should be aware of the high rate of adverse neonatal outcome in macrosomic fetuses, even in the absence of diabetes mellitus.